The life of seaweed farmers in Selakan Island, Semporna, Sabah - Jamal, Nurul Auni; Abdul Rahman, Ahmad Tarmizi (2015)
The beauty of Sabah with surrounding islands is undeniable and receives world-wide recognition. The revenue generated through solar resources, mineral from the ocean and ecosystem which allows Sabah to increase the economic resources through a wide range of industries including tourism, fisheries, agriculture and aquaculture. One of the aquacultural activities carried out is seaweed cultivation. This study focused on seaweed industry’s importance to social and community development. The study examines the life of seaweed farmers, which includes the location and geographical structure, the history of the race, social organization, activity, employment, social activities and community, and religion. Documentation of the life of seaweed farmers is an entrybased studies conducted with ethnography which is a suitable method to understand their culture, values, and religion. Data were collected through structured and unstructured interviews and participating observation which was carried out for almost two years. Data collections were also conducted periodically. The study provides an overview of the life of seaweed farmers in Selakan Island that is very different from farmers on the mainland.